Characterization of water soluble polysaccharides from bamboo shoot (Gigantochloa levis blanco merr) and their prebiotic potential - Muhammad Nurul Azmi, Aida Firdaus (2012)
Health benefits of bamboo shoots are often neglected as limited study was carried out to reveals its medicinal properties. Increasing demands in functional foods like prebiotics have driven many researches to isolate these functional ingredients from natural sources. Therefore this research was conducted as to explore the prebiotic potential of bamboo shoots from Gigantochloa levis. Characterization on its compositions, molecular weight, solubility, digestibility, intrinsic viscosity,rheological properties, thermal stability and morphological properties were also covered. Hot water extraction (90 0C) of water soluble polysaccharides extracted from the shoots of Gigantochloa levis (which was named as Bamboo Shoots Crude Polysaccharides, BSCP) was found to be 3.27 ± 0.18 % of dry basis, with molecular weight of about 7.49 kDa, while other purified sub-fractions (F1 to F5) were 1550.96, 1471.63, 1685.78, 1691.61 and 1551.67 Da respectively. BSCP was composed of glucose, galactose and arabinose as the major sugar components with the molar ratio of 10 : 5 : 4 (50.51 ± 1.16, 25.11 ± 0.31 and 19.81 ± 0.52 % molar respectively). The percentage of xylose, mannose, rhamnose and fucose in crude BSCP were however found to be relatively low; 2.05 ± 0.03, 1.77 ± 0.25, 0.62 ± 0.53 and 0.14 ± 0.02 % molar respectively. It also posses good solubility in water (99.81 ± 0.01 % solubility at 5 % (w/v) of BSCP) and its non-digestibility towards artificial human gastric juices was proven to be significantly higher (> 99 %) as to compare with the commercial fructooligosaccharides (FOS) (98 %). This might be due to the presence of (1→3),(1→4)-β-glucan in BSCP as elucidated through Fourier Transform Infra Red (FTIR) spectrum as well as Nuclear Magnetic Resonance (NMR). Fingerprint of BSCP gathered through structural analysis using FTIR showed that BSCP contains polysaccharide with traces of phenolic and uronic acids presence. Intrinsic viscosity of BSCP was 6.89 dl/g, with a rod-like conformation presumed in the dilute domain through the measurement of power law model. The onset of molecular entanglements or the critical concentration, C* for BSCP was 0.88 g/dl,while the relative chain stiffness for BSCP was found to be 0.3086, which was about ten times greater than pectin and alginate. This value showed a more flexible chain of BSCP polymer, which was not aligned to the conformation of BSCP presumed through power law model measurement. This is because rod-like polymer tends to have a stiff chain. Atomic Force Microscopy (AFM) analysis conducted for morphological studies of BSCP was however elucidated the conformation of BSCP to be globular rather than rod-like polymer. Rheological test conducted had confirmed the weak gel properties of BSCP. It was found to be a heat-setting gel, where gel is formed upon heating of a solution. Thermal analysis using Differential Scanning Calorimetry (DSC) also proves the weakness of BSCP gelling properties, with a very small enthalpy value obtained (0.03 to 0.37 mJ). In vitro fermentation conducted using BSCP as a carbon source gave a positive indicator as a potential prebiotic. BSCP was found to potently support the growth of B. animalis, B. longum and L. acidophilus. On top of that, BSCP was able to suppress the growth of Salmonella sp. pH of Trypticase Peptone Yeast (TPY) medium supplemented with BSCP and FOS were seen to decrease as an indication of bacterial growth. Lactic acid and SCFA produced by the probiotic strains supplemented with BSCP were also found to be higher as compared to FOS, even though there was no significant trend noted. Results obtained throughout this research showed that BSCP meets most of prebiotic characteristics, which is highly resistance to the artificial gastric juice, able to be fermented by the intestinal microbiota like bifidobacterium and lactobacilli while suppressing the growth of pathogens as well as producing SCFA which later could enhance the host health indirectly.